Financial Management and Policy / Third Edition - Van Horne James C (Prentice Hall Inc, 1974)
Preface, Introduction, The Goals and Functions of Finance, Concepts in Valuation, Portfolio Theory and Efficient Market Considerations, Investment in Assets and Acceptance Criterion, Principles of Capital Budgeting, Cost of Capital, The Evaluation of Risky Investments, Financing and Dividend Policies, Theory of Capital Structure,Dividends and Valuation, Dividend Policy of the Firm, Long-Term Financing, Investment Banking and Common Stock, Long-Term Debt and Preferred Stock, Convertible Securities and Warrants, Management of Liquidity and Current Assets, Liquidity Structure of Assets and Liabilities, Management of Accounts Receivable, Inventory Management, Short and Intermediate - Term Financing, Short-Term Loans, Lease Financing, Expansion and Contraction, Mergers and Consolidations, The Tools of Financial Analysis and Control, Financial Ratio Analysis, Analysis of Operating and Financial Leverage, Appendixes, Index.
Preface, Introduction, The Goals and Functions of Finance, Concepts in Valuation, Portfolio Theory and Efficient Market Considerations, Investment in Assets and Acceptance Criterion, Principles of Capital Budgeting, Cost of Capital, The Evaluation of Risky Investments, Financing and Dividend Policies, Theory of Capital Structure,Dividends and Valuation, Dividend Policy of the Firm, Long-Term Financing, Investment Banking and Common Stock, Long-Term Debt and Preferred Stock, Convertible Securities and Warrants, Management of Liquidity and Current Assets, Liquidity Structure of Assets and Liabilities, Management of Accounts Receivable, Inventory Management, Short and Intermediate - Term Financing, Short-Term Loans, Lease Financing, Expansion and Contraction, Mergers and Consolidations, The Tools of Financial Analysis and Control, Financial Ratio Analysis, Analysis of Operating and Financial Leverage, Appendixes, Index.